The Effect of Person-Job Fit on Perceived Employability of Internship Participants - Nur Aulia Rahmah Prayugo; Idha Rahayuningsih (Universitas Negeri Medan, 2026)
This study aimed to examine the effect of person-job fit on perceived employability among interns. This correlational quantitative study involved all active interns at PT Swabina Gatra using a saturated sampling technique. Data collection utilized valid and reliable Likert scale questionnaires. The descriptive statistical results showed that the distribution of the person-job fit variable was dominated by the moderate category (74.0%), followed by high (14.0%) and low (12.0%) categories. Meanwhile, perceived employability was also dominated by the moderate category (72.0%), followed by low (16.0%) and high (12.0%) categories. Hypothesis testing proved that person-job fit has a positive and significant effect on perceived employability, with a contribution effect (R-Square) of 55.2%. The alignment between individual competencies and job demands is the main determinant in shaping interns' subjective beliefs regarding their career competitiveness. This research recommends a career briefing program based on psychological strengthening through personal SWOT analysis to improve the adaptability and perceived employability of industrial interns.